2016
DOI: 10.1108/cr-04-2015-0024
|View full text |Cite
|
Sign up to set email alerts
|

The impact of implementing green supply chain management practices on corporate performance

Abstract: Purpose The purpose of this research is to investigate the implementation of green supply chain management (GSCM) practices and its impact on corporate performance (CP). The research in particular examines the results of implementing a set of GSCM practices on different dimensions of the CP. Design/methodology/approach This study, being the first of its kind in the Middle East, developed a research model to test the relationship between four main GSCM practices namely, eco-design, green purchasing, environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
192
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(235 citation statements)
references
References 84 publications
7
192
2
1
Order By: Relevance
“…The results obtained indicated that the adoption of certain practices inside GSCM enables positive financial outcomes. This relationship was once again visited by Younis, Sundarakani, and Vel () who also found positive relationships between the adoption of GSCM practices and firm performance.…”
Section: Literature Reviewmentioning
confidence: 82%
See 1 more Smart Citation
“…The results obtained indicated that the adoption of certain practices inside GSCM enables positive financial outcomes. This relationship was once again visited by Younis, Sundarakani, and Vel () who also found positive relationships between the adoption of GSCM practices and firm performance.…”
Section: Literature Reviewmentioning
confidence: 82%
“…Other accounting variables used for financial performance were 3‐year average profit value (Younis et al, ); growth rate of sales (Tan et al, ); average month revenues (Lucato et al, ); revenue, profit, and rate trend (Oh et al, ); asset to total debt ratio (Paun, ); and weighted average cost of capital (Atan et al, ).…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Third, the environmental dimension of sustainable GS has a significant and positive relationship with social performance of the firm [151,152]. Lee (2016) [152] proposes that environmentally and socially responsible SCM are positively related to relationship commitment, which further positively affects each dimension of supplier performances i.e.…”
Section: Cluster 5: Interrelationship Of Three Aspects Of Sustainabilitymentioning
confidence: 99%
“…environmental, social and operational performance. Younis et al (2016) [151] indicate that the environmental practice exerts a positive influence on social performance. Specifically, green purchasing plays a role in improving the economic performance, while reverse logistics practices are found to impact the social performance (i.e., improved corporate image, social commitment, preserve the environment and enhanced employee job satisfaction) of the firm positively (ibid).…”
Section: Cluster 5: Interrelationship Of Three Aspects Of Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation